2019
DOI: 10.3389/fneur.2019.00046
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Magnetic Resonance Imaging Reveals the Relationship Between the Control of Vertigo and Decreases in Endolymphatic Hydrops After Endolymphatic Sac Drainage With Steroids for Meniere's Disease

Abstract: Meniere's disease is a common disease, that presents with recurrent vertigo and cochlear symptoms. The pathology of Meniere's disease was first reported to involve endolymphatic hydrops in 1938. The endolymphatic sac is thought to have a role to keep the hydrostatic pressure and endolymph homeostasis for the inner ear. As a surgery for intractable Meniere's disease, endolymphatic sac drainage with intraendolymphatic sac application of large doses of steroids is performed to control the endolymphatic hydrops an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…In the present study, all 3 patients in the EDB group for whom reversal of EH was con rmed were found to have improved hearing, revealing a cause-effect relationship between EH and hearing function. However, with the 4 patients in the EDD group for whom reversal of EH was con rmed, hearing improved in only one patient, worsened in one, and was stabilized in the other two, suggesting no correlation between the changes in hearing function and the volume of EH after sac drainage surgery, a nding that was consistent with previous reports [26][27][28]. In the former case (EBD), the reversal of EH was found to be a delayed effect associated with the surgery that progressed over time, which was likely to be linked with physiological recovery in the homeostasis of the endolymph.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, all 3 patients in the EDB group for whom reversal of EH was con rmed were found to have improved hearing, revealing a cause-effect relationship between EH and hearing function. However, with the 4 patients in the EDD group for whom reversal of EH was con rmed, hearing improved in only one patient, worsened in one, and was stabilized in the other two, suggesting no correlation between the changes in hearing function and the volume of EH after sac drainage surgery, a nding that was consistent with previous reports [26][27][28]. In the former case (EBD), the reversal of EH was found to be a delayed effect associated with the surgery that progressed over time, which was likely to be linked with physiological recovery in the homeostasis of the endolymph.…”
Section: Discussionsupporting
confidence: 88%
“…As presented in Figs. 2-5, the MRI technique used in the present study had an equal or superior resolution to other techniques reported in previous literature [14,15,[26][27][28]. The comparison of serial MRI scans, which were obtained from multiple section planes in the same ear between the before and after treatment, could clearly identify the dynamic changes of EH, showing an objective marker for assessing the effects of treatment in MD.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, Ito et al reported a positive correlation between the control of vertigo and the decrease in the volume of EH, and no correlation between changes in the hearing function and the volume of EH following sac drainage surgery [ 46 , 47 ]. Higashi-Shingai et al also described that the presence of vestibular EH and the frequency of vertigo attacks significantly decreased following surgery, but no significant improvement in the presence of cochlear EH or the SP/AP ratio of ECochG was observed [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently only a few reports on the visualization of EH after treatment have been published. Subsiding of EH has recently been described after oral acetazolamide, IT corticosteroids, and endolymphatic sac surgery [91][92][93]. However, Gürkov et al found no effect of standard-dose oral betahistine on the degree of EH during a 7-month followup period [94].…”
Section: Clinical Application and Future Perspectivesmentioning
confidence: 99%